Вони відкривали лазерну епоху (до 90-річчя академіка НАН України М.С. Бродина) - Негрійко, А.М. (Вісник НАН України, 2021)
30 вересня виповнюється 90 років відомому вченому в галузі фізики твердого тіла, нелінійної оптики та квантової електроніки, лауреату Ленінської премії (1966), Державних премій СРСР (1982), УРСР (1974) та України (1994) в галузі науки і техніки, заслуженому діячеві науки і техніки України (1992), повному кавалеру ордена «За заслуги», лауреату премії ім. К.Д. Синельникова НАН України (1998), академіку-секретарю (1990—1998) Відділення фізики і астрономії НАН України, директору (1987—2006) Інституту фізики НАН України (нині — почесному директору), доктору фізико-математичних наук (1963), професору (1968), академіку НАН України (1982) Михайлу Семеновичу Бродину. September 30 marks the 90th anniversary of the famous scientist in the field of solid state physics, nonlinear optics and quantum electronics, winner of the Lenin Prize (1966), State Prizes of the USSR (1982), UkrSSR (1974) and Ukraine (1994) in Science and Technology, Honored Worker of Science and Technology of Ukraine (1992), full holder of the Order of Merit, winner of the K.D. Sinelnikov Prize of the NAS of Ukraine (1998), Academician-Secretary (1990-1998) of the Department of Physics and Astronomy of the NAS of Ukraine, Director (1987-2006) of the Institute of Physics of the NAS of Ukraine (now Honorary Director), Doctor of Physical and Mathematical Sciences (1963), Professor (1968), Academician of the NAS of Ukraine (1982) Mykhailo S. Brodyn.